Effectiveness of Coenzyme Q10 Supplementation for Reducing Fatigue: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - I-Chen Tsai; I-Chen Tsai; I-Chen Tsai; Chih-Wei Hsu; Chih-Wei Hsu; Chun-Hung Chang; Chun-Hung Chang; Chun-Hung Chang; Ping-Tao Tseng; Ping-Tao Tseng; Ping-Tao Tseng; Ke-Vin Chang; et al. (Frontiers in Pharmacology, 2022)
Coenzyme Q10 (CoQ10) is a popular nutritional supplement, an antioxidant and an essential component of the mitochondrial electron transport chain. Several clinical studies have suggested that fatigue can be reduced by antioxidant supplementation. However, the data on this topic has been sparse to date. Hence, we conducted this meta-analysis with the aim of investigating the effectiveness of fatigue reduction via CoQ10 supplementation. More specifically, we searched electronic databases for randomized controlled trials (RCTs) published from the database inception to January 2022. A random effects model was implemented to conduct the meta-analysis among 13 RCTs (with a total of 1,126 participants). As compared with the placebo groups evaluated in each RCT, the CoQ10 group showed a statistically significant reduction in fatigue scores (Hedges’ g = −0.398, 95% confidence interval = −0.641 to −0.155, p = 0.001). The directions of the treatment effects were consistent between the healthy and diseased participants. Compared with the placebo group, the effect of reducing fatigue was statistically significant in the subgroup using the CoQ10-only formulation but not in the subgroup using CoQ10 compounds. The results of our meta-regression demonstrate that increases in the daily dose (coefficient = −0.0017 per mg, p < 0.001) and treatment duration (coefficient = −0.0042 per day, p = 0.007) of CoQ10 supplementation were correlated with greater fatigue reduction. There was only one adverse (gastrointestinal) event in the 602 participants who underwent the CoQ10 intervention. Based on the results of this meta-analysis, we conclude that CoQ10 is an effective and safe supplement for reducing fatigue symptoms.Systematic Review Registration:https://inplasy.com/inplasy-2022-1-0113/, identifier INPLASY202210113